AFM lithography and fabrication of multifunctional nanostructures with perovskite oxides. (18th September 2009) - Li, Run-Wei
Recent progress on atomic force microscopy (AFM) lithography on perovskite oxides, including doped SrTiO3 single crystalline substrates and artificial perovskite manganite films, are reviewed systematically. SrTiO3 is the commercial substrate extensively used for epitaxially growing perovskite oxide films and also a popular film material for fabricating functionalised devices. Perovskite manganite films are very promising candidate materials for spintronic devices and magnetic sensors. By combining AFM lithography and other techniques, such as film deposition, photo lithography, and wet etching etc., multifunctional nanodevices/nanostructures composed of perovskite oxides can be created.